Pathology of autoimmune hepatitis - Covelli, Claudia; Sacchi, Diana; Sarcognato, Samantha; Cazzagon, Nora; Grillo, Federica; Baciorri, Francesca; Fanni, Daniela; Cacciatore, Matilde; Maffeis, Valeria; Guido, Maria (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Autoimmune hepatitis (AIH) is a relatively rare non-resolving chronic liver disease, which mainly affects women. It is characterized by hypergammaglobulinemia, circulating autoantibodies, interface hepatitis on liver histology and a favourable response to immunosuppression. The putative mechanism for the development of autoimmune hepatitis is thought to be the interaction between genetic predisposition, environmental triggers and failure of the native immune system. AIH still remains a major diagnostic and therapeutic challenge, mainly because it is a very heterogeneous disease. Prompt and timely diagnosis is crucial since, if left untreated, AIH has a high mortality rate. Histological demonstration of hepatitis is required for the diagnosis of AIH and, therefore, liver biopsy is mandatory in the initial diagnostic work-up, before treatment. In this review, we summarize the histological features of AIH with the main aim of highlighting the most important clinical-pathological hallmarks useful in the routine diagnostic practice.